Carvacrol from Plectranthus Amboinicus as Antibiofilm and Anti-Inflammatory Compound - J.R., Likhitha; Simon, Simi; Veeraraghavan, V.; Thomas, Tessy Anu (Asian Journal of Biological and Life Sciences, 2026)
Background: The present study investigated the bioactive potential of Plectranthus amboinicus leaf extract with a focus on the isolation, characterization, and functional evaluation of its principal phytochemical constituents. Materials and Methods: Leaves were subjected to Soxhlet extraction using methanol, followed by purification through Thin-Layer Chromatography (TLC) and column chromatography. Phytochemical characterization using GC–MS and FTIR analyses identified Carvacrol as the major constituent of Fraction 2. Results: Enhanced bioactivity was observed upon fractionation, with Fraction 2 exhibiting the most pronounced effects. Carvacrol accounted for approximately 32% of its composition. Carvacrol demonstrated significant antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa, along with potent antibiofilm efficacy, exhibiting low IC₅₀ values comparable to the standard antibiotic tetracycline. Mechanistic investigations revealed that Carvacrol effectively inhibited key virulence factors of P. aeruginosa, including elastase production, pyocyanin synthesis, and swarming motility. Additionally, Carvacrol exhibited notable immunomodulatory and anti-inflammatory properties in RAW 264.7 macrophage cell lines by modulating critical inflammatory enzymes such as Cyclooxygenase (COX), Lipoxygenase (LOX), and Myeloperoxidase (MPO). Conclusion: Overall, these findings highlight Carvacrol as a multifunctional phytochemical with substantial antibacterial, antibiofilm, and immunomodulatory activities, supporting its therapeutic potential for biomedical and pharmaceutical applications.
Keywords: Plectranthus amboinicus; Carvacrol; GC-MS; FTIR; Thin Layer Chromatography; S; aureus; P. aeruginosa